Theory and Applications of Colloidal Suspension Rheology / Ed. - Mewis, Jan (Newyork : Cambridge University Press, 2021)
"An essential text on practical application, theory, and simulation, written by an international coalition of experts in the field and edited by the authors of Colloidal Suspension Rheology. This up-to-date work builds upon the prior work as a valuable guide to formulation and processing, as well as fundamental rheology of colloidal suspensions. Thematically, theory and simulation are connected to industrial application by consideration of colloidal interactions, particle properties, and suspension microstructure. Important classes of model suspensions including gels, glasses, and soft particles are covered so as to develop a deeper understanding of industrial systems ranging from carbon black slurries, paints and coatings, asphalt, cement, and mine tailings, to natural suspensions such as biocolloids, protein solutions, and blood. Systematically presenting the established facts in this multidisciplinary field, this book is the perfect aid for academic researchers, graduate students, and industrial practitioners alike"--
Keywords: Colloids -- Viscosity; Colloids -- Transport properties; Rheology; TECHNOLOGY & ENGINEERING / Chemical & Biochemical